Yay’s Dental Education Model as an Effort to Improve Knowledge, Attitudes, and Behavior of Parents of Children with Autism Spectrum Disorder - Yayuk Fathonah; Diyah Fatmasari; Bedjo Santoso (Jurnal Kesehatan Gigi, 2022)
Children with autism have difficulty in terms of social interaction, communication and language, behaviour, imagination, emotional disturbances, sensory perception and motor aspects. Causes common understanding in children with autism, namely difficulty in brushing teeth. More than 60% of parents reported that their children with autism could not brush their teeth. They only brushed their teeth once per day. Another study revealed that 57% of autistic children did not want to put a toothbrush in their mouth, 37% of children were afraid to brush their teeth, and 55% of children did not like the taste or texture of toothpaste. Nearly 47% of children with autism do not understand the importance of brushing their teeth, and half of these children cannot stay still while brushing their teeth. Yay's Dental Education model is an alternative to developing a dental and oral health education model that can be used at home by involving the role of parents. The educational model consists of the Tell-Show-Feel-Do (TSFD) method, Visual Pedagogy, PECS media and Positive Reinforcement (PR). The method in this research is Research and Development with a Quasy Experiment model with a control group pre and post-test design). Based on the results of statistical tests, stated that this model was effective in increasing the mother's knowledge (p = 0.004), attitudes (p = 0.000) and actions (p = 0.001) about maintaining oral health in children with autism. Mothers' knowledge, attitudes and actions can change habits to apply excellent and correct tooth brushing techniques in children. Guidance and mentoring of mothers to maintain dental and oral hygiene are necessary so that children can get used to brushing their teeth and keep healthy teeth and mouth independently.